Angat Reservoir monthly operations using an optimization-simulation model with seasonal autoregressive model to forecast inflows - Tabios, Guillermo Q. III
This paper presents an optimization-simulation model for monthly allocation of the multi-purpose Angat Reservoir for water supply to Metro Manila, irrigation water to Bulacan, hydropower generation and flood control purposes. This reservoir operation scheme employs a dynamic, anticipatory or hedging operation policy over a 6-month planning horizon. This is in contrast to the existing procedure in which the reservoir releases are based on target storage or rule curves defined by upper and lower rule curves (storages) that vary on monthly basis. This paper also presents a monthly forecasting model of reservoir inflows using a seasonal autoregressive model implemented with sequential model parameter estimation scheme to efficiently update the model parameters as new information becomes available. It is demonstrated in this study that the Angat Reservoir monthly allocation procedure using an optimization-simulation model performs better than the currently employed reservoir rule curve-based operations in terms of satisfying water demand and hydropower generation based on 58 years of historical reservoir inflows as well as using forecasted inflows.
Keywords: Optimization-simulation model